Guides for Cultural Observation and Valuation - Ferro Medina, Germán (Instituto Carlos Arbeláez Camacho para el patrimonio arquitectónico y urbano, 2014)
The following article offers a set of six guides for cultural observation and valuation. They are tools within the frameworkof a proposal for a methodology for the identification or recognition of cultural heritage. The guidelines are foundedon a horizon of analysis of historical and geographical aspects, thus giving value to cultural landscapes. The papershould be seen as a pedagogical exercise that reflects the experience of several social science disciplines. As anintroduction, the article attempts to conceptualize the subject matter of cultural landscapes, central to this edition.